2022
DOI: 10.20473/jisebi.8.1.61-70
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Emotion in Indonesian Tweets: A Term-Weighting Scheme Study

Abstract: Background: Term-weighting plays a key role in detecting emotion in texts. Studies in term-weighting schemes aim to improve short text classification by distinguishing terms accurately. Objective: This study aims to formulate the best term-weighting schemes and discover the relationship between n-gram combinations and different classification algorithms in detecting emotion in Twitter texts. Methods: The data used was the Indonesian Twitter Emotion Dataset, with features generated through different n-gram comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Previous studies also used KNN to analyze 5 emotion labels, namely anger, happiness, sadness, love, and fear, using TF-IDF. The accuracy results achieved were still below the accuracy results obtained in this study, which is 0.51% (Nugroho et al, 2022). Furthermore, this study also conducted sentiment analysis on emotions, but it calculated the accuracy for each label separately, resulting in accuracy above 90% (Kaur & Bhardwaj, 2019).…”
Section: Results and Discussion Knn 6 Label Using Tf-idfmentioning
confidence: 61%
“…Previous studies also used KNN to analyze 5 emotion labels, namely anger, happiness, sadness, love, and fear, using TF-IDF. The accuracy results achieved were still below the accuracy results obtained in this study, which is 0.51% (Nugroho et al, 2022). Furthermore, this study also conducted sentiment analysis on emotions, but it calculated the accuracy for each label separately, resulting in accuracy above 90% (Kaur & Bhardwaj, 2019).…”
Section: Results and Discussion Knn 6 Label Using Tf-idfmentioning
confidence: 61%
“…Other studies examining machine learning models with 6 labels or more also achieved accuracies below 70%. In a prior study [73], accuracies of 50% for KNN with TF-IDF, 66% for SVM with TF-IDF, and 55% for Decision Tree with TF-ICF were reported. Another research [74] found accuracies of 61% for naï ve Bayes, logistic regression, SVM, 64% for Decision Tree, and 57% for Adaboost.…”
Section: Discussionmentioning
confidence: 98%
“…A more extensive, less common feature space is an n-gram. A larger n increases information and computational expense [21]. In this research, we combine the unigram, the bigram, and the trigram forms of the n-gram.…”
Section: N-grammentioning
confidence: 99%
“…IDF gives greater weight to terms that appear more frequently in the document, regardless of whether those words are used often or infrequently [22] [23]. TF-IDF is now the most popular text classification and document categorization scheme [24] [21].…”
Section: E Term Frequency -Inverse Document Frequency (Tf-idf)mentioning
confidence: 99%